Marine Co-Management: Marine Governance in Improving the Welfare of Fishermen in Jembrana, Bali - Lailatus Sah’ro; Agus Trihartono; Hary Yuswadi; Selfi Budi Helpiastuti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is motivated by the uniqueness of marine governance for the welfare of fishermen in the perspective of co-management. An alternative model or solution to marine management problems. Implementing this model requires collaborative management by combining elements of the user community (fishermen groups, fisheries entrepreneurs and others) and the government. This research is focused on Pengambengan Village, Negara District, Jembrana Regency, Bali Province. The type of this research is qualitative with a descriptive approach. Data collection techniques used include direct observation (observation), interviews (interviews), and data collection through documents and triangulation techniques. The results of the study indicate that marine governance for the welfare of fishermen can be pursued with a co-management model. The co-management model can unite related institutions, especially fishermen and the government as well as other stakeholders in every resource management process starting from planning, implementation, utilization and supervision. Marine co-management as an effort to increase marine potential that can be utilized optimally by fishermen.